Linkage and transportation availability towards intention to stay in business among senior in Tamu Sabah - Sidah Idris; Kasim Md. Mansur; Nurfarhana Mohd. Saidi (Zes Rokman Resources, 2021)
In Sabah, TAMU is the famous local market which as a medium for social meeting point for both rural and urban communities besides also acting as an important local economic hub with rich cultural infusion tracing back long before the independence of Malaysia. Some traders travel far from another district in a different geographical division to do business activities at TAMU. This study was conducted to examine whether road linkage and transportation availability among older TAMU traders along west coast of Sabah have effect on the intention to remain in current business activities than younger people. The study examined the direct relationship of three indicators; accessibility, efficiency of infrastructure and transport linkage indicators to TAMU traders’ intention to stay in their current TAMU business. This study was also conducted to explore the moderating effect of age on the relationship between linkage and transportation availability to intention to remain in current business activities among senior TAMU traders in Sabah. The collection of quantitative data was obtained through the manual distribution of questionnaires to the respondents at TAMU site in the three separate districts: Penampang, Kota Kinabalu and Ranau. The collected data were then analysed using SPSS and SmartPLS 3.0 software. This study was conducted to provide knowledge regarding the relationship between the dependent and independent variables which adds to the existing literature on both road linkage and transportation availability in local industrial or business attraction area such TAMU in Sabah. The findings of this study would be beneficial for the government, local authorities, academics, TAMU traders and business owners to understand the relationship between the intention and the independent variables.